1998
DOI: 10.1182/blood.v91.7.2264
|View full text |Cite
|
Sign up to set email alerts
|

JAK2 and JAK1 Constitutively Associate With an Interleukin-5 (IL-5) Receptor α and βc Subunit, Respectively, and Are Activated Upon IL-5 Stimulation

Abstract: The human interleukin-5 receptor (hIL-5R) consists of a unique α subunit (hIL-5Rα) and a common β subunit (βc) that activate two Janus kinases (JAK1 and JAK2) and a signal transducer and activator of transcription (STAT5). The precise stoichiometry of the hIL-5R subunits and the role of JAK kinases used in IL-5 signaling were investigated. We analyzed the interaction between hIL-5Rα and βc by immunoprecipitation using anti–hIL-5Rα and anti-βc monoclonal antibodies. The binding of JAK1 and JAK2 to each hIL-5R s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…IL‐5 activates at least three different signaling pathways, including the JAK2/STAT5, Btk, and Ras/ERK pathways. The JAK2 and JAK1 tyrosine kinases are constitutively associated with IL‐5RA and βc, respectively, and are activated by IL‐5 stimulation 28. According to the structural model of the IL‐5•IL‐5RA•βc octamer (4:2:2 ratio) [Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IL‐5 activates at least three different signaling pathways, including the JAK2/STAT5, Btk, and Ras/ERK pathways. The JAK2 and JAK1 tyrosine kinases are constitutively associated with IL‐5RA and βc, respectively, and are activated by IL‐5 stimulation 28. According to the structural model of the IL‐5•IL‐5RA•βc octamer (4:2:2 ratio) [Fig.…”
Section: Discussionmentioning
confidence: 99%
“…IL‐5 stimulation induces rapid tyrosine phosphorylation of various cellular proteins, including βc, the SH2/SH3‐containing proteins Vav, HS1, Shc, and so forth . Btk, the Btk‐associated molecules, and the JAK1/JAK2, STAT1/STAT5, PI3K, and MAP kinases, activates downstream signaling molecules,24, 26–28 and leads to the maintenance of the survival and functions of B cells and eosinophils. The activation of JAK2 and STAT5 is essential for IL‐5‐dependent signal transduction 29–31.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…. These signal transduction pathways are catalysed by Janus kinases (JAK) , JAK/signal transducer and activator of transcription (STAT) , mitogen‐activated protein kinase (MAPK) , the extracellular signal‐regulated kinases (ERK1 and ERK2) , Lyn tyrosine kinase , phosphoinositide 3‐kinase and nuclear factor κB (NF‐κB) . IL‐5 can also induce JAK‐binding protein expression in eosinophils, which constitutes a negative feedback regulatory mechanism of IL‐5 signalling .…”
Section: Interleukin‐5/interleukin‐5r Interactionsmentioning
confidence: 99%
“…Interleukin‐5 (IL‐5) is an important member of the IL‐2 superfamily, and mainly secreted by immune cells such as macrophages (Mø) and lymphocytes (especially the CD4 + T lymphocytes), but less secreted by smooth muscle cells and endothelial cells (Sewell et al, 1998; Deo et al, 2010; Takatsu, 2011; Park et al, 2017). IL‐5 binds to IL‐5 receptor (IL‐5R) on target cells, activates the Janus Kinase (JAK) 1/2 and signal transducer and activator of transcription 1/5 (STAT1/5) signaling pathway and initiates downstream signals (Takaki et al, 1994; Kouro et al, 1996; Ogata et al, 1998). Previous studies have indicated that IL‐5 participates in a variety of diseases by regulating immune effects and the inflammatory response.…”
Section: Introductionmentioning
confidence: 99%